In Vitro Behavior of Boron-Doped Baghdadite/Poly(vinylidene fluoride) Membrane Scaffolds Produced via Non-Solvent Induced Phase Separation - Mutlu, Busra; Demirci, Fatma; Erginer, Merve; Duman, Seyma (Wiley-V C H Verlag Gmbh, 2025)
This study explores the potential of boron-doped baghdadite (BAG) powders incorporated into poly(vinylidene fluoride) (PVDF)-based membrane scaffolds for bone tissue engineering applications. The aim is to enhance the scaffolds' microstructure, surface wettability, thermal behavior, mechanical properties, and biological performance. Composite scaffolds are fabricated by integrating the powders into the PVDF matrix, yielding scaffolds with enhanced material characteristics and functionality. The incorporation of the powders significantly enhances the hydrophilicity of the scaffolds, as evidenced by a notable reduction in contact angle measurements. Mechanical analyses demonstrate that the addition of boron-doped BAG powders reduces the tensile strength and elongation at the break of PVDF scaffolds, attribute to increased pore size, reduced crystallinity, and structural heterogeneity, though the values remain within the range of human cancellous bone. Furthermore, in vitro bioactivity studies reveal the superior apatite-forming ability of the composite scaffolds, indicating their enhanced potential for biomineralization. The results of the cellular adhesion assays indicate an enhanced affinity and proliferation of cells on the membrane scaffolds, which is indicative of improved biocompatibility. In conclusion, the developed PVDF-based membrane scaffolds, reinforce with BAG powders, show promise as effective alternatives to traditional bone graft materials, offering scalable and versatile solutions for regenerative medicine.
Keywords: biocompatibility; boron-doped baghdadite; membrane scaffolds; NIPS (non-solvent induced phase separation); PVDF